2021
DOI: 10.1002/mdc3.13319
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Brain in Parkinson's Disease

Abstract: The central cholinergic system includes the basal forebrain nuclei, mainly projecting to the cortex, the mesopontine tegmental nuclei, mainly projecting to the thalamus and subcortical structures, and other groups of projecting neurons and interneurons. This system regulates many functions of human behavior such as cognition, locomotion, and sleep. In Parkinson's disease (PD), disruption of central cholinergic transmission has been associated with cognitive decline, gait problems, freezing of gait (FOG), falls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 136 publications
(262 reference statements)
1
33
0
Order By: Relevance
“…Alternatively, because the neurochemistry of PD is complex and involves several other neurotransmitter systems than dopamine, it could be the case that taste recognition in PD patients is additionally influenced by non-dopaminergic pathology ( Brichta et al, 2013 ). In line with this idea, Cecchini et al (2019) recently demonstrated that chemosensory impairments in PD were associated with mild cognitive impairment, a symptom of PD that has also been linked to non-dopaminergic neurochemical abnormalities ( Pasquini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…Alternatively, because the neurochemistry of PD is complex and involves several other neurotransmitter systems than dopamine, it could be the case that taste recognition in PD patients is additionally influenced by non-dopaminergic pathology ( Brichta et al, 2013 ). In line with this idea, Cecchini et al (2019) recently demonstrated that chemosensory impairments in PD were associated with mild cognitive impairment, a symptom of PD that has also been linked to non-dopaminergic neurochemical abnormalities ( Pasquini et al, 2021 ).…”
Section: Discussionmentioning
confidence: 88%
“…However, the implications of our findings extend beyond FOG and reveal a missing piece of the puzzle to the pathophysiology of PD. Given the inherent complexity of PD and our current understanding of the contributions of the dopaminergic system to pathophysiology of PD, it is likely that other neuromodulatory systems (ie, cholinergic, serotonergic) are involved in the diversity of symptoms of PD 63,64 . It has previously been established that both acute and chronic anxiety plays a distinct role in PD 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Given the inherent complexity of PD and our current understanding of the contributions of the dopaminergic system to pathophysiology of PD, it is likely that other neuromodulatory systems (ie, cholinergic, serotonergic) are involved in the diversity of symptoms of PD. 63,64 It has previously been established that both acute and chronic anxiety plays a distinct role in PD. 65 Other studies have established that anxiety worsens other symptoms of PD, such as bradykinesia 66 and tremor.…”
Section: Discussionmentioning
confidence: 99%
“…The development of novel cholinergic fluorine-based PET tracers, including 18F-Fluoroethoxybenzovesamicol (18F-FEOBV) binding to the vesicular acetylcholine transporter [ 102 ], has enabled rapid advances in the last five years to pinpoint the role of basal forebrain cholinergic dysfunction for falls and freezing of gait in PD [ 103 ], as well as multi-domain cognitive impairment [ 104 ], as reviewed in [ 105 ]. Indeed, in contrast with 11C-MP4A or 11C-donepezil, which indicates cholinesterase activity in both the pre- and post-synaptic compartment and synaptic cleft, but with low sensitivity in subcortical structures, 18F-FEOBV binds with high affinity to the vesicular transporter, notably in the striatum [ 106 ].…”
Section: Neurotransmitter Imagingmentioning
confidence: 99%